(3Sff CHj OGhOs - (3SdjeGf Hf GdCTYK Hf ESMGb Hf HTjQ GdGROj GdSLSJGfj, CHh OGhO,J (B275 (3g` s ((3eMeO Hf ESeGYjd GdgfOi GdOgdhi s)
(3ChdgG (B:s
(3Chd cJGH GdMO hcJGH eG LGA ai GdMce ajef EQJO s
(3BNQgG (B:s
(3BNQg ef (B" (3HGH ai bJGd GddUhU (B" (3bhdg (B: (3aEf QShd Gddg Udi Gddg Ydgj hSde bGd (B:" (3ETaYhG JDLQhG , hCNHQfG CHh eYeQ Yf CHj ehSi Yf GdfHi Udi Gddg Ydjg hSde eKdg Je cJGH GdSff HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HGdhQbI GdCNjQI SeGYGJ hbQGAGJ hELGRGJ ai GdbQf GdKGef GdgLQis
(3hHChdgG HebOGQ NeS hQbGJ NW eZGjQs
(3hYdi MhGTjgG JYdjbGJ s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs